Discrimination and genetic diversity among cultivated olives of Greece using RAPD markers - Nikoloudakis, Nikolaos; Banilas, Georgios; Gazis, F.; Hatzopoulos, P.; Metzidakis, J. (My University, 2003)
Random amplified polymorphic DNA (RAPD) markers were used to study the genetic diversity and to discriminate among 33 Greek olive (Olea europaea L.) cultivars. Three feral forms from Crete and five foreign cultivars recently introduced into Greece were also included. Nineteen primers were selected which produced 64 reproducible polymorphic bands in the 41 olive genotypes studied, with an average of 3.4 informative markers per primer. The RAPD markers resulted in 135 distinct electrophoretic patterns, with an average of 7.1 patterns per primer. Based on either unique or combined patterns, all genotypes could be identified. Genetic similarities between genotypes were estimated using the Dice similarity index and these indicated that a high degree of diversity exists within the Greek olive germplasm. Using the unweighted pair-group method (UPGMA) most cultivars were clustered into two main groups according to their fruit size or commercial use (table or olive oil). However, poor correlation was detected between clustering of cultivars and their principal area of cultivation. RAPD marker data were subjected to nonmetric multidimentional scaling (NMDS) which produced results similar to those of the UPGMA analysis. The results presented here contribute to a comprehensive understanding of cultivated Greek olive germplasm and provide information that could be important for cultural purposes and breeding programs.
Keywords: Cultivars; Diversity; Olea europaea; Polymorphism